IMPROVEMENT OF BULK HETEROJUNCTION SOLAR CELLS TROUGH AU ION IMPLANTATION INTO PEDOT:PSS LAYER - Badilla, Dennis Gerardo Brenes (2014)
Organic solar cells show great potential to become a commercially available technology for renewable clean energy production due to their attractive properties. Inexpensive materials and manufacturing processes, including classical roll-to-roll fabrication, as well as the ability to produce flexible, low weight, semitransparent devices are some of the advantages organic photovoltaics provide. Addressing the most common issues in these new technologies, i.e., the low efficiencies of devices and rapid degradation of materials, could bring a realistic alternative for the photovoltaic industry. In this work, the performance of P3HT:PCBM based bulk heterojunction solar cells modified through low energy gold ion implantation in the hole transporting layer, the PEDOT:PSS, is studied. Reference solar cells without gold were also fabricated and characterized for comparison. Through field emission scanning electron microscopy (FESEM) micrographs, the formation of gold nanoparticles (AuNPs) in the PEDOT:PSS has been shown layer for the highest implantation doses used. Absorbance measurements of PEDOT:PSS films before and after gold implantation further confirmed this result. TRIDYN and SRIM simulation programs estimated shallow gold implantations of ~3 nm underneath the PEDOT:PSS films surface. Current-voltage (JxV) characteristics of reference solar cells under AM 1.5 illumination presented the uncommon S-shaped curves, an abnormal deviation from typical JxV curves. This was attributed to PEDOT:PSS degradation due to oxygen and water exposure, which reduced its work function significantly. As a result, deteriorated parallel and series resistances were obtained in reference devices, which ultimately reduced their field factors and power conversion efficiencies. This abnormal behavior was consistently eliminated with the introduction of AuNPs near the PEDOT:PSS/Active-layer interface, leading to the rectification of the illuminated JxV curves of modified solar cells and the reestablishment of cell parameters. Consequently, outstanding improvements in the field factors and power conversion efficiencies were observed in these devices. This was attributed to enhancement (and prevention from the reduction) of the PEDOT:PSS work function layer due to the presence of AuNPs, which rearranged the energy levels at the interface to a more favorable state: higher electron blocking and lower hole extraction barriers.